A self-regulation strategy for triboelectric nanogenerator and self-powered wind-speed sensor. (May 2022) - Zou, Hong-Xiang; Zhao, Lin-Chuan; Wang, Qiong; Gao, Qiu-Hua; Yan, Ge; Wei, Ke-Xiang; Zhang, Wen-Ming
Abstract: Small wind harvesting can be integrated with sensors for self-powered environmental ecological monitoring, climate monitoring, natural disaster monitoring and on-site infrastructure monitoring, which is of great importance for protecting and improving the living environment of human beings. However, the randomness and irregularity of wind seriously limit the application of wind energy harvesting and self-powered sensing technology. In this paper, a self-regulation strategy for triboelectric nanogenerator (TENG-SS) is proposed and a self-powered wind-speed sensor is achieved. By rationally designing the centrifugal and nonlinear magnetic forces, the separation and contact degrees of the functional materials of TENG can be adjusted automatically for different wind speeds. When the wind speed is low, the aerodynamic force is small, and the frictional resistance is also small due to self-regulation, the device is easy to start, and the wear is small; at high wind speed, the aerodynamic force overcomes greater frictional resistance to generate more electricity. Based on the working principle of TENG-SS, a dynamic model is established and verified experimentally, and the influence of the key parameters on the performance of the TENG-SS is analyzed. Furthermore, the prototypes of TENG with and without the self-regulation strategy are compared in a natural wind environment for 21, 600 s, which proves that the proposed TENG-SS exhibits better performance and robustness. The proposed TENG-SS is used for self-powered wind speed measurements and wireless information transmission. This study provides a new perspective for improving the performance of TENG in the natural environment through self-regulation strategy. Graphical Abstract: ga1 Highlights: A self-regulation strategy with centrifugal force and magnetic force is proposed. Higher power and robustness of TENG-SS are verified by natural wind experiments. The electromechanical coupling dynamic model of the proposed system is established. The self-powered wind speed measurement and wireless transmission are realized.